Elucidating the Origins of High Preferential Crystal Orientation in Quasi‐2D Perovskite Solar Cells (Adv. Mater. 5/2023). Issue 5 (2nd February 2023) - Lehner, Lukas E.; Demchyshyn, Stepan; Frank, Kilian; Minenkov, Alexey; Kubicki, Dominik J.; Sun, He; Hailegnaw, Bekele; Putz, Christoph; Mayr, Felix; Cobet, Munise; Hesser, Günter; Schöfberger, Wolfgang; et al.
Abstract : Perovskite Solar Cells In article 2208061, Lukas E. Lehner, Martin Kaltenbrunner, and co‐workers report the controlled nucleation of quasi‐2D perovskites at the liquid–air interface of the precursor solution. Restricting the initial crystal growth to the surface of the liquid results in highly aligned perovskite thin films with improved charge transport, enabling efficient solar cells with excellent stability.